(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Hypertensive crisis is a life-threatening clinical condition characterized by a sudden and severe elevation of blood pressure that may lead to acute damage of vital organs. Timely recognition and appropriate emergency management are crucial to prevent irreversible complications such as stroke, myocardial infarction, acute renal failure, and aortic dissection. This article examines the concept of hypertensive crisis, its classification, pathophysiology, and evidence-based emergency care strategies. Emphasis is placed on rapid assessment, pharmacological interventions, monitoring, and outcome evaluation in emergency settings. The study highlights current clinical approaches and provides practical recommendations for improving emergency care outcomes.